6x-10=3x+5+3(3x-5)

Simple and best practice solution for 6x-10=3x+5+3(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-10=3x+5+3(3x-5) equation:


Simplifying
6x + -10 = 3x + 5 + 3(3x + -5)

Reorder the terms:
-10 + 6x = 3x + 5 + 3(3x + -5)

Reorder the terms:
-10 + 6x = 3x + 5 + 3(-5 + 3x)
-10 + 6x = 3x + 5 + (-5 * 3 + 3x * 3)
-10 + 6x = 3x + 5 + (-15 + 9x)

Reorder the terms:
-10 + 6x = 5 + -15 + 3x + 9x

Combine like terms: 5 + -15 = -10
-10 + 6x = -10 + 3x + 9x

Combine like terms: 3x + 9x = 12x
-10 + 6x = -10 + 12x

Add '10' to each side of the equation.
-10 + 10 + 6x = -10 + 10 + 12x

Combine like terms: -10 + 10 = 0
0 + 6x = -10 + 10 + 12x
6x = -10 + 10 + 12x

Combine like terms: -10 + 10 = 0
6x = 0 + 12x
6x = 12x

Solving
6x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
6x + -12x = 12x + -12x

Combine like terms: 6x + -12x = -6x
-6x = 12x + -12x

Combine like terms: 12x + -12x = 0
-6x = 0

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 9x+3-5x=(2x+5) | | 8a+32=2a | | 5-8x=13+7(x-3) | | 5=8n-7n | | -23k+63=-45 | | 6(1d-4)=4d-18 | | 4(x-5)-2x=4 | | 1=2x-3x | | 8a+32=8a | | -134=20x-34 | | 15+w=8 | | 2(x-5)=8x-5 | | 3(n+2)+5=6(n+4)+n | | -4s+2l=50 | | 5(2x+1)=3(3x-2) | | 7x-2(3x+5)=2 | | (3x-1)=3+8x-11 | | 6x=5(x-2) | | 4(-11)+x(3x-4)-6(x+6)=y | | 78=-2m+6+m | | 2(3x-4)=5x-6 | | 3x-1=-8+8x | | 3x-33=15 | | 7x+25=235 | | 122+32+n=180 | | -1x+4=8.0 | | =19-15(-9+17k) | | 8-81+-2n=-75 | | x+3=-x+7 | | -5x+10=2x+31 | | 7+25x=235 | | 6=-x+4x |

Equations solver categories